Faktor yang mempengaruhi porsi pembiayaan bagi hasil pada Bank Pembiayaan Rakyat Syariah - Pramono, Setya (CV. Kurnia Grup, 2023)
This study examines conceptual and empirical models of Manager Skills, Sharia Compliance, Sharia Bank Characteristics, Manager Perception of Sharia Bank Internal SDI, Manager Perception of Customer Characteristics, Manager Perception of Regulatory Existence, Manager Perception of Government Support for Profit Sharing Financing Portion at Sharia People's Financing Bank. The selection of the research site was carried out by proportional simple random sampling technique. The sampling technique used in his research was purposive sampling. In this study there were 36 BPRS in DIY and Central Java, then five people were taken as respondents for each BPRS consisting of the Board of Directors, Sharia Supervisory Board, Marketing Manager, Operations Manager (Financing Manager) and Customer Service. So the number is 180 (One Hundred and Eighty) respondents. The object of assessment is the Operations Manager/Financing Manager, considering that this research is related to the portion of profit sharing financing. The results showed that 1) The conceptual skills of managers have a positive effect on the portion of profit sharing financing in Sharia BPR 2) The technical skills of managers have a positive effect on the portion of profit sharing financing in Sharia BPR 3) The social skills of managers have a positive effect on the portion of profit sharing financing in Sharia BPR 4) Manager's perception of the internal SDI of Islamic banks has a positive effect on the portion of profit sharing financing in Sharia BPR 5) Manager's perception about the existence of regulations has a positive effect on the portion of profit sharing financing in Sharia BPR 6) Manager's perception of government support has a positive effect on the portion of profit sharing financing in Sharia BPR 7) There is no influence of the characteristics of Islamic banks on the portion of profit sharing financing in Sharia BPR 8) There is no influence of sharia compliance on the portion of profit sharing financing in Sharia BPR 9) No influence of managers' perception of characteristics customers against the portion of profit sharing financing at BPR Syariah.